The effect of tactile and verbal guidance during scapulothoracic exercises: An EMG and kinematic investigation - Staker, Justin L.; Evans, Amanda J.; Jacobs, Laura E.; Ebert, Thomas P.; Fessler, Noah A.; Saini, Gaura; Ludewig, Paula M. (Journal of electromyography and kinesiology, 2022)
Clinician-led training through tactile and verbal guidance to improve muscle activity and joint motion are a common but understudied focus of therapeutic interventions for shoulder pain. The purpose of this study was to determine if clinician guidance changes scapulothoracic muscle activity and kinematics compared to unguided shoulder exercises. Eleven participants with shoulder pain were studied. Electromyographic (EMG) sensors were placed on the serratus anterior and upper and lower trapezii. Scapulothoracic and sternoclavicular kinematics were collected using electromagnetic sensors. Five common resisted shoulder exercises were performed with the following guidance: unguided, combined (verbal and tactile cues), and verbal guidance only. One-way repeated measures ANOVAs determined the effect of guidance versus unguided conditions for each exercise. Nine of ten combinations of exercise and guidance techniques demonstrated a significant effect of guidance for either muscle activity or joint kinematics. The guidance condition with the most frequent significant improvements across all variables was the combined condition. The exercises with the most frequent significant improvements across all variables were the external rotation exercises. Variables improved most frequently were: upper:lower trapezius EMG ratio (up to 11%), sternoclavicular elevation (up to 6°) and scapulothoracic internal rotation positioning (up to 8°), and sternoclavicular retraction displacement (up to 5°). Shoulder muscle activity and kinematics during exercises can be modified by tactile and verbal guidance. Most improvements in muscle activity occurred with verbal guidance during external rotation exercises. Most improvements in joint positioning and movement occurred with combined guidance during external rotation exercises.